Zasoby indywidualne i systemowe w diadzie mistrz-uczeń = The individual and system resources in the master-student relation - Klimas-Kuchtowa, Ewa (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The theoretical bases for presented paper are: holistic conception of human being as bio-psycho-social unit, ideas of cognitive psychology and of positive psychology. An education is here understood as an interaction between an educator (sometimes it can be a parent also) and a pupil.
Keywords: mistrz-uczeń w nauczaniu muzyki; interakcja nauczania; cechy przydatne w efektywnym nauczaniu i uczeniu się; master?pupil interaction in education of music; traits needed in effective teaching and learning